India and the Indian Ocean, 1500-1800 - Pearson, M. N. (Michael Naylor), 1941-; Das Gupta, Ashin (Calcutta ; New York : Oxford University Press, 1987)
Contributed articles.
Includes bibliographies and index.
Keywords: India -- Commerce -- Indian Ocean Region -- History; Indian Ocean Region -- Commerce -- India -- History